2009
DOI: 10.1093/humrep/den501
|View full text |Cite
|
Sign up to set email alerts
|

In GnRH antagonist/rec-FSH stimulated cycles, advanced endometrial maturation on the day of oocyte retrieval correlates with altered gene expression

Abstract: In stimulated cycles, endometrial gene expression on the day of oocyte retrieval discriminates between women with and without histologically advanced endometrial maturation exceeding 3 days and supports histological dating results by Noyes' criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 32 publications
3
69
2
2
Order By: Relevance
“…Previous studies (Kolibianakis et al, 2002;Ubaldi et al, 1997) with endometrial biopsies on the day of oocyte retrieval and following embryo transfer demonstrated that an endometrial advancement of more than 3 days never resulted in a clinical pregnancy. From an earlier study in our group (Van Vaerenbergh et al, 2009), these findings were confirmed on the gene expression level with microarrays. It was found that endometrial samples taken on the day of oocyte retrieval from patients in a GnRH antagonist/ rec-FSH stimulation protocol for IVF with embryo transfer all showed an advanced endometrial maturation and that the samples with an advanced endometrium of more than 3 days clustered together in a separate molecular profile.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Previous studies (Kolibianakis et al, 2002;Ubaldi et al, 1997) with endometrial biopsies on the day of oocyte retrieval and following embryo transfer demonstrated that an endometrial advancement of more than 3 days never resulted in a clinical pregnancy. From an earlier study in our group (Van Vaerenbergh et al, 2009), these findings were confirmed on the gene expression level with microarrays. It was found that endometrial samples taken on the day of oocyte retrieval from patients in a GnRH antagonist/ rec-FSH stimulation protocol for IVF with embryo transfer all showed an advanced endometrial maturation and that the samples with an advanced endometrium of more than 3 days clustered together in a separate molecular profile.…”
Section: Discussionsupporting
confidence: 66%
“…The Wnt/β-catenin signalling pathway has been described before in different implantationrelated and endometrial receptivity studies (Tulac et al, 2003;Van Vaerenbergh et al, 2009). …”
Section: Discussionmentioning
confidence: 92%
“…A premature rise (>1.5 ng/mL) in progesterone may occur in spite of using GnRH agonist or antagonist for pituitary suppression during COS and is often associated with increased ovarian response (i.e., high estrogen levels and follicle numbers). Although the exact cause-andeffect mechanisms of a premature progesterone rise is not fully understood, it has been suggested to involve the advancement of endometrial development and in altered endometrial gene expression [7][8][9][10]. In some studies, cycles with elevated progesterone levels before ovulation induction have been associated with reduced pregnancy and live birth outcomes, suggestive of reduced endometrial receptivity and placentation [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Данные результаты позволили сделать заключение о необходимости отмены переноса эмбрионов, их криоконсервации и переносе в последующем цикле [1]. В исследовании [53] продемонстрировано, что экспрессия ге-нов эндометрия различна у пациенток с морфологическим опережением созревания эндометрия в день получения ооцитов более чем на 3 дня и без него. …”
Section: молекулярно-генетические индукторы эндометрия в стимулированunclassified